Between Strangeness and an Alternative Buddhist Lifestyle: An Expression of Religious Non-Conformity in Consumer Culture - Bártová, Zuzana (My University, 2022)
This study contributes to the sociological understanding of the social perceptions of religious engagement and its self-presentation in consumer culture. Drawing on three years of comparative ethnographic research on the Buddhist lifestyle in five different organisations in France and the Czech Republic, it reveals that Buddhist engagement, through its practices, is considered peculiar or even potentially dangerous by the participants’ environment. Remarks of the people surrounding them reflect typical features of the popular understanding and the literature on sects, cults and new religious movements and express social pressure to respect different social norms. They also partly represent social demands to adopt a conformist lifestyle because of their often individualised and activity-centred character. At the same time, Buddhist practitioners’ self-presentation of their engagement is in line with alternative lifestyle discourses since it challenges different social practices, forms of sociability, ethics and other values. The importance, diversity and positive image associated with this alternative stance can be considered an expression of the value of non-conformity that reflects the individualism and disdain of conformism typical of consumer culture.
Mezi zvláštností a alternativním buddhistickým životním stylem: Vyjádření náboženské nekonformity ve spotřební kultuře
Keywords: convert Buddhism; sects; France; Czech Republic; religious lifestyle; konvertní Buddhismus; sekty; Francie; Česká republika; náboženský životní styl